PELATIHAN PEMELIHARAAN KEBERSIHAN DAN PENYULUHAN KESEHATAN DI TANGERANG, BANTEN [WORKSHOP ON HYGIENE AND HEALTH CARE AT TANGERANG, BANTEN] - Marcelia Sugata; Astia Sanjaya; Hans Victor; Reinhard Pinontoan (Universitas Pelita Harapan, 2020)
Health is closely related to hygiene and nutritious food consumption. However, the practice of monitoring personal hygiene and consuming nutritious food has not been carried out properly, especially among elementary school students. Therefore, this community service activity (PKM) aimed to increase children's awareness about the importance of proper hygiene practices and the importance of adequate nutritional intake. Besides paying attention to personal hygiene, children also need to be aware to environmental hygiene, for example by reducing plastic waste and utilizing organic waste for composting. To achieve this goal, this PKM was divided into two sessions, one session was about counseling on personal hygiene and health for elementary school students in grade 1, while another session was about composting training for elementary school students in grades 5-6. The results of the survey conducted before and after the activity showed that this counseling was successfully increase the awareness of students about the good practice of maintaining personal hygiene and health. In addition, composting training provided students with knowledge and understanding that composting does not require special skills; but requires considerable effort and time. BAHASA INDONESIA ABSTRACT: Kesehatan sangat erat kaitannya dengan kebersihan dan konsumsi makanan bergizi. Namun, seringkali praktek menjaga kebersihan diri dan mengonsumsi makanan bergizi belum dilakukan secara baik dan benar, terutama di kalangan siswa sekolah dasar. Oleh karena itu, kegiatan pengabdian kepada masyarakat (PkM) ini bertujuan untuk meningkatkan kesadaran anak-anak mengenai pentingnya praktek kebersihan yang benar serta pentingnya asupan gizi yang cukup. Selain memperhatikan kebersihan diri, anak-anak juga perlu diajarkan untuk memperhatikan kebersihan lingkungan, misalnya dengan mengurangi sampah plastik dan memanfatkan sampah organik untuk pembuatan kompos. Untuk mencapai tujuan tersebut, PkM ini dibagi menjadi dua bagian, yaitu penyuluhan mengenai kebersihan diri dan kesehatan untuk siswa SD kelas 1 serta pelatihan pembuatan kompos untuk siswa SD kelas 5-6. Hasil survei yang dilakukan sebelum dan sesudah kegiatan menunjukkan bahwa kegiatan penyuluhan yang dilakukan berhasil meningkatkan kesadaran para siswa mengenai praktek pemeliharaaan kebersihan diri dan kesehatan yang benar. Selain itu, pelatihan membuatan kompos berhasil memberikan pengetahuan dan pemahaman pada para siswa bahwa pembuatan kompos tidak memerlukan keahlian khusus, namun memerlukan tenaga dan waktu yang cukup banyak.